Investigation of Antibiofilm Activities from Marine Sponges’ Crude Extract of Pulau Bidong, Terengganu, Malaysia - Gazali Mohamad; Nur Izzah Alissa Wan Rosli Wan; Sarah Mohd Zahidi Siti; Amira Jamaludin Nur; Bakar Kamariah; Saidin Jasnizat (BIO Web of Conferences)
Biofilm, intricate microbial communities adhering to submerged surface, pose a significant challenge across various sectors. Conventional approaches relying on harsh chemical or mechanical removal have drawback. Marine organisms like sponges, with their diverse secondary metabolites, offer a promising avenue for developing sustainable solutions. This study investigated the antibiofilm potential of crude extracts from four marine sponges (Stylissa carteri, Haliclona amboinensis, Hymeniacidon sp., and Xestospongia testudinaria) against Vibrio parahaemolyticus and Pseudomonas aeruginosa biofilms. Crystal Violet staining quantified biofilm formation and removal. Well diffusion assays assessed antibacterial activity. Haliclona amboinensis and Hymeniacidon sp. extracts displayed antibiofilm effects against V. parahaemolyticus biofilm. The IC50 values for the activity were 0.1 mg/mL and 0.19 mg/mL, respectively. Notably, the Hymeniacidon sp. extract exhibited bactericidal activity whereas H. amboinensis lacked this effect. Interestingly, both extracts effectively removed pre-formed V. parahaemolyticus biofilms against P. aeruginosa, H. amboinensis displayed antibiofilm activity (IC50 = 2.8 mg/mL) without bactericidal effects. However, this extract did not impact pre-established P. aeruginosa biofilms. The study suggests H. amboinensis is a promising source for new antibiofilm agents. It effectively inhibits biofilm formation without killing bacteria. Further research is needed to identify the active compounds and their mechanisms for developing targeted therapies.